Digital natives of the labor market: Generation Z as future leaders and their perspectives on leadership - Yılmaz, Betül; Dinler Kısaçtutan, Elvin; Gürün Karatepe, Seçil (Frontiers in Psychology, 2024)
Introduction: Today's labor market is comprised of different generations and in the near future, the majority of it will consist of Generation Z. In this respect, it is of great importance to know the perspective of Generation Z, which will take its place in leadership positions in organizations, on leadership and what kind of leader they will be. The present study probes to investigate how Generation Z will become a leader and their perspective on leadership. In this regard, the study aims to offer suggestions and guidance to the literature and organizations by providing information on what kind of leaders they will be as well as knowing the characteristics of Generation Z leaders.Methods: In the study conducted Generation Z, employed in the IT sector, semi-structured interviews were held with 13 participants. While analyzing the data obtained from the interviews, the MAXQDA 2020 program was utilized and the thematic analysis method was applied.In our findings about how Generation Z will be leaders in the future, two themes were identified, which include intra-organizational communication and working conditions. In the light of findings on the leadership of Generation Z, the sub-themes of being supportive, empathetic, egoless, managing people well and managing with love and respect were reached on the theme of intraorganizational communication. On the other hand, on the theme of working conditions, sub-themes such as providing training, offering payment according to output, preferring flexible working hours, being friendly, assigning appropriate work to the employee, being fun and not giving importance to gender were identified.The results revealed that Generation Z prefers managing their team with a peopleoriented approach when they take leadership positions. From their perspective, the leader should understand and value his employees. Leaders who know the expectations of Generation Z will contribute to their organizations. In addition, organizations should improve their leadership skills by providing leadership training for Generation Z, who will be leaders in the future. In this way, they will make investment both in their leaders and their organizations.